Renal Cell Carcinoma presented with An Intramedullary Spinal Cord Metastasis : A Case Report (Bangladesh Critical Care Journal, 2016)
Intramedullary spinal cord metastasis is one of the rare manifestations of systemic neoplasm causing diagnostic dilemma. Here we report a case of metastatic renal cell carcinoma presented initially as spinal cord lesion. A 62 years old Bangladeshi gentleman presented with spastic paraparesis, bone pain with unexplained weight loss. After thorough examination & detailed investigations we found intramedullary spinal cord metastasis with infiltrative lesion on bone scan. We confirmed renal cell carcinoma after doing CT Abdomen and histopathology as primary site of lesion. He was treated by radical nephrectomy & radiotherapy. It is imperative that clinicians should be cautious of occult carcinoma as the cause of suspicious intramedullary spinal cord lesion.Bangladesh Crit Care J March 2016; 4 (1): 51-53